Eye Movements in Gaze Interaction - Emilie Møllenbach; John Paulin Hansen; Martin Lillholm (Bern Open Publishing, 2013)
Gaze as a sole input modality must support complex navigation and selection tasks. Gaze interaction combines specific eye movements and graphic display objects (GDOs). This paper suggests a unifying taxonomy of gaze interaction principles. The taxonomy deals with three types of eye movements: fixations, saccades and smooth pursuits and three types of GDOs: static, dynamic, or absent. This taxonomy is qualified through related research and is the first main contribution of this paper. The second part of the paper offers an experimental exploration of single stroke gaze gestures (SSGG). The main findings suggest (1) that different lengths of SSGG can be used for interaction, (2) that GDOs are not necessary for successful completion, and (3) that SSGG are comparable to dwell time selection.